LEADERSHIP AND ACADEMIC QUALITY AT THE FACULTY OF ADMINISTRATIVE SCIENCES OF THE UCAYALI NATIONAL UNIVERSITY - Palomino Ochoa, Rosario Leonor (2019)
The objective of the research was to determine the incidence of the leadership of the authorities and teachers in the academic quality of the Faculty of Administrative Sciences of the National University of Ucayali during 2014. The type of research was descriptive - correlational. The research design used was Non-Experimental. The population was conformed by 350 students of the Faculty of Administrative Sciences of the National University of Ucayali during the year 2014. The sample was conformed by 183 students of the Faculty of Administrative Sciences of the National University of Ucayali during the year 2014. The results Arrived in the present investigation demonstrate that the leadership, proactive, democratic and strategic of the authorities and teachers of the Faculty of Administrative Sciences of the National University of Ucayali, has a positive impact on the academic quality during 2014, since society perceives that produced graduates: with effective management of administrative management, entrepreneurs and innovators, generators of companies that contributed to the change and transformation of the social, economic and technological reality of Ucayali. The conclusion reached in the research was: the leadership in the academic management carried out 1, Docente de la Universidad Privada de Pucallpa, Ucayali, Perú. Cultura Viva Amazónica - Revista de Investigación Científica - Pucallpa, Perú. 3 (3) 2018 39 Vicerrectorado de Investigación by the authorities and the teachers of the Faculty of Administrative Sciences of the National University of Ucayali, therefore, the current society needs the formation of leaders that propitiate a intellectual, emotional integration, consolidate your work team strengthening leadership focused on strengthening the academic. KEYWORDS: Leadership, Academic Quality, Leadership Practices.